Family Economic Resilience Strategy Through Strengthening Women's Social Capital Network - Rahel Widiawati Kimbal (AIBPM Publisher, 2021)
This research aims to find a strategy for family economic resilience through strengthening the form of the social capital networks in small industry enterprises (UIK) in Kanonang village. This is because the economic resilience of the family is the bastion of a strong and sturdy nation. This study uses a qualitative research method with a case study whose data collection techniques use triangulation in the form of observation, interviews and documentation. For data analysis using the Spradley step-by-step model. The results found in the field regarding the strategy of family economic resilience through strengthening the form of women's social capital networks at UIK were found through natural activities between women business owners and women workers in the field in terms of: (1) Collective spirit (2) Information disclosure (3) social cohesive maintenance (4) ease of accessibility to raw materials (5) Circulation of product marketing (6) Established good communication with the environment (7). Family and business financial management. Family economic resilience by strengthening the form of social capital networks should continue to be explored and maintained so that they can develop for the advancement of women as an active resource for family strength in small industrial enterprises in Indonesia.